2017
DOI: 10.18632/oncotarget.20556
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of pressure-activated cancer cell adhesion by FAK-derived peptides

Abstract: Forces within the surgical milieu or circulation activate cancer cell adhesion and potentiate metastasis through signaling requiring FAK-Akt1 interaction. Impeding FAK-Akt1 interaction might inhibit perioperative tumor dissemination, facilitating curative cancer surgery without global FAK or AKT inhibitor toxicity. Serial truncation and structurally designed mutants of FAK identified a seven amino acid, short helical structure within FAK that effectively competes with Akt1-FAK interaction. Adenoviral overexpre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 48 publications
1
15
0
Order By: Relevance
“…Extracellular pressure treatment. Cells (50,000 cells/well) were seeded into 24 well plates that were then subjected to 15 mmHg increased extracellular pressure for 30 min at 37˚C in a mixture of 5% CO 2 with 95% room air in a pre-warmed air tight box with inlet and outlet valves and a pressure gauge, as described previously (17,24,27). It has been previously reported that this technique, if the box is appropriately pre-warmed, allows for the control temperature, pressure and oxygen partial pressure within the cell culture medium.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Extracellular pressure treatment. Cells (50,000 cells/well) were seeded into 24 well plates that were then subjected to 15 mmHg increased extracellular pressure for 30 min at 37˚C in a mixture of 5% CO 2 with 95% room air in a pre-warmed air tight box with inlet and outlet valves and a pressure gauge, as described previously (17,24,27). It has been previously reported that this technique, if the box is appropriately pre-warmed, allows for the control temperature, pressure and oxygen partial pressure within the cell culture medium.…”
Section: Methodsmentioning
confidence: 99%
“…Adhesion assay. Our previous studies performed cell counting via optical microscope (23,28) and Tag-it dye (Tag-it Violet Proliferation Cell Tracking Dye; Biolegend, Inc., San Diego, CA, USA) staining method (24,27) for cell counting and have revealed that dye staining methods are more objective as they do not require the observer to select which microscopic fields to count and are more accurate as they compensate for any unevenness of distribution of cells across the well. Therefore, the adherent cells were not imaged, and only their optical densities were measured.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations